REAL-WORLD EXPERIENCE OF DULAGLUTIDE THERAPY IN A SINGLE TERTIARY CENTER - Omar, Mohd Rahman; Wahab, Norasyikin A; Jaafar, Rohana J; Hann, Kang Waye; Ismail, Farhana Binti; Mustafa, Norlaila; Sukor, Norlela; Kamaruddin, Nor Azmi (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Glucagon-like peptide-1 receptor agonists such as dulaglutide are recommended in the overall management of type 2 diabetes (T2D). The clinical responses to dulaglutide as add-on therapy for patients with T2D are varied. METHODOLOGY The study objective was to observe the outcome of real-world practice using add-on dulaglutide to existing treatment for patients with uncontrolled T2D. We performed a retrospective analysis of all patients who received dulaglutide 1.5 mg weekly from 2018 to 2021 with at least four months of therapy. Only patients with metabolic parameters at baseline and at least on the second visit were included. RESULTS A total of 77 patients received dulaglutide therapy from 2018 to 2020; of these, only 68 had complete data for analysis. The median age was 48 years [interquartile range (IQR) 41, 57.8]. Forty-six (65.7%) were female. The median duration of therapy was 6.7 months (IQR 4, 8). There was a significant reduction of HbA1c by 1.6%, from 8.6% (IQR 7.45, 9.6) to 7.0% (IQR 6.2, 7.7) (p<0.001). There were significant changes in weight profiles: median weight reduction of 2.0 kg (IQR 0.2, 5.15), from 89.2 kg (74.2, 97.6%) to 88.3 kg (IQR 77.1, 95) (p<0.001); waist circumference (WC) reduction from 106 cm (IQR 100, 115) to 104.5 cm (IQR 95.5, 112.5) (p=0.015); and body mass index (BMI) reduction from 34.3 kg/m2 (IQR 30, 37.3) to 33.9 kg/m2 (IQR 29.5, 37.5) (p=0.001). CONCLUSION Treatment with dulaglutide as additional therapy for uncontrolled T2D reduced HbA1c, weight, WC and BMI as early as four months of therapy.